PENGARUH KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI INOVASI DAN KINERJA KARYAWAN (Studi Kasus Pada KANWIL PT. PEGADAIAN (PERSERO) DENPASAR) - Putra Salain, Putu Pradiva; Wardana, Made (Buletin Studi Ekonomi, 2016)
The influence of leadership on organizational, Transactional and employee perfomnce (case study an Kanwil PT Pegadaian Persero, Denpasar. The purpose of this research to determine the effect of transformational and transactional leadership on organizational innovation culture and employee performance. The number of samples in this study were 131 employees sampled. Hypothesis testing using structural model analysis techniques (SEM analysis), with the tools of SPSS (statistical package for social science) and AMOS (analysis of moment structure). The results showed that: (1) transformational leadership has a positive effect on the performance of employees in the Office (2) transactional leadership has a positive effect on employee performance at the Office of  (3) the positive effect of transformational leadership on organizational culture of innovation at Office (4) the positive effect of transactional leadership on organizational culture in the Office, and (5) organizational culture of innovation has a positive effect on employee performance in the Office.   Keywords : transformational leadership, transactional leadership, organizational culture of innovation and employee performance
Keywords: transformational leadership, transactional leadership, organizational culture of innovation and employee performance